De' Lalaps - Arimi, Hanafi; Amsah, Siti Maufifah; Gadhapi, Normohamadsha; Makmur, Nurul Faznila; Hamri, Nur Hazriani (2013)
We are starting our own business as partners and all of us decided to name our business as De' Lalaps. The main idea was to produce and serve Nasi Lalap and Fresh Juice. We also have our side service such as delivery service to our customer. Each of the partners is also acting as the head department with one person as the general manager. We will run this business at Taman Indah Permai as it is a develop area and has gain the attention from the people across Kota Kinabalu Sabah and IPTA students. We seized the opportunity because it will surely add up the competition and choices for the people to make.